Analgesic efficacy of sleep-promoting pharmacotherapy in patients with chronic pain: a systematic review and meta-analysis. (6th January 2023) - Andersson, Emelie; Kander, Thomas; Werner, Mads U.; Cho, Joshua H.; Kosek, Eva; Bjurström, Martin F.
Abstract : Supplemental Digital Content is Available in the Text. Meta-analytic data indicate that targeting of the sleep–pain interface through a sleep-promoting medication may decrease pain intensity in chronic pain populations. Abstract: Dysregulation of sleep heightens pain sensitivity and may contribute to pain chronification. Interventions which consolidate and lengthen sleep have the potential to improve pain control. The main objective of this systematic review was to examine the effects of sleep-promoting pharmacotherapy on pain intensity in patients with chronic pain. Multiple electronic databases were searched from inception to January 2022 to identify relevant randomized controlled trials (RCTs). Two independent reviewers screened titles, abstracts, and full-text articles; extracted data; and assessed risk of bias for each included study. The GRADE approach was used to determine the strength of evidence. The search identified 624 articles. After full-text screening, 10 RCTs (n = 574 randomized participants) involving 3 pharmacologic interventions (melatonin, zopiclone, and eszopiclone) and 7 different chronic pain populations were included. Minimum clinically significant pain reduction ≥30% was reported in 4 studies. There is low-quality evidence (downgraded due to inconsistency and imprecision) that 2 to 8 weeks treatment with a sleep-promoting medication alone or in combination with an analgesic (6 trials, n = 397) decreases pain intensity compared with placebo or the same analgesic treatment alone (SMD −0.58 [95% confidence interval −1.00, −0.17], P = 0.006). Analyses of associations between changes in sleep and pain outcomes were only provided in 2 articles, with inconsistent findings. Notably, pain-relieving effects were most consistent in melatonin trials. Only 3 studies implemented polysomnography to obtain objective sleep measures. Low-quality evidence indicates that pharmacologic sleep promotion may decrease pain intensity in chronic pain populations. More research is needed to fully understand the influence of sleep-targeting interventions on pain control.